TKSA-MC: A web server for rational mutation through the optimization of protein charge interactions - Contessoto, Vinícius G. [UNESP]; de Oliveira, Vinícius M. [UNESP]; Fernandes, Bruno R. [UNESP]; Slade, Gabriel G. [UNESP]; Leite, Vitor B. P. [UNESP] (My University, 2018)
The TKSAMC is a web server which calculates protein charge–charge interactions via the Tanford–Kirkwood Surface Accessibility model with the Monte Carlo method for sampling different protein protonation states. The optimization of charge–charge interactions via directed mutations has successfully enhanced the thermal stability of different proteins and could be a key to protein engineering improvement. The server presents the electrostatic free energy contribution of each polar-charged residue to the protein native state stability. Specific residues are suggested to be mutated for improving thermal stability. The choice of a residue is based on its fraction of side chain exposed to solvent and its positive free energy contribution, which tends to destabilize the protein native state. Any residue energy contribution can be shown as a function of pH condition. The web server is freely available at UNESP (São Paulo State University - DF/IBILCE): http://tksamc.df.ibilce.unesp.br and also on GitHub https://github.com/contessoto/tksamc.
Keywords: charge–charge interaction; protein engineering; protein thermal stability; rational mutation; TSKA model; web server